Mesenchymal iron deposition is associated with adverse long‐term outcome in non‐alcoholic fatty liver disease. (28th May 2020) - Eder, Sebastian K.; Feldman, Alexandra; Strebinger, Georg; Kemnitz, Jana; Zandanell, Stephan; Niederseer, David; Strasser, Michael; Haufe, Heike; Sotlar, Karl; Stickel, Felix; Paulweber, Bernhard; Datz, Christian; et al.
Abstract: Background & Aims: Approximately one‐third of patients with non‐alcoholic fatty liver disease (NAFLD) show signs of mild‐to‐moderate iron overload. The impact of histological iron deposition on the clinical course of patients with NAFLD has not been established. Methods & Results: For this retrospective study, 299 consecutive patients with biopsy‐proven NAFLD and a mean follow‐up of 8.4 (±4.1; range: 0.3‐18.0) years were allocated to one of four groups according to presence of hepatic iron in the reticuloendothelial system (RES) and/or hepatocytes (HC): 156 subjects (52%) showed no stainable iron (NONE), 58 (19%) exclusively reticuloendothelial (xRES), 19 (6%) exclusively hepatocellular (xHC) and 66 (22%) showed a mixed (HC/RES) pattern of iron deposition. A long‐term analysis for overall survival, hepatic, cardiovascular or extrahepatic‐malignant events was conducted. Based on multivariate Cox proportional hazards models any reticuloendothelial iron was associated with fatal and non‐fatal hepatic events. Specifically, xRES showed a cause‐specific hazard ratio (csHR) of 2.4 (95%‐CI, 1.0‐5.8; P = .048) for hepatic as well as cardiovascular fatal and non‐fatal events combined (csHR 3.2; 95%‐CI, 1.2‐8.2; P = .015). Furthermore, the mixed HC/RES iron pattern showed a higher rate of combined hepatic fatal and non‐fatal events (csHR 3.6; 95%‐CI, 1.4‐9.5; P = .010), while xHC iron deposition was not associated with any defined events. Conclusions: The presence of reticuloendothelial‐accentuated hepatic iron distribution patterns is associated with detrimental long‐term outcomes reflected in a higher rate of both liver‐related and cardiovascular fatal and non‐fatal events.